Combination Of Breast Care And Oxytocin Massage Of Breastfeeding Mothers In Infant Weight Gain - Ria Gustirini; Inge Anggi Anggraini (Jurnal Kesehatan Prima, 2020)
The perception that the supply of milk production is less than  30-80% of breastfeeding mothers is the main reason mothers stops breastfeeding their babies. Breast milk is a source of fat and protein that is important for the growth and nutrition of infants. Increased breast milk secretion has a  very positive impact on the baby's weight gain. One technique to increase  milk production,  among others,  by doing  breast care and oxytocin massage.  Breast  Care aims  to expedite  blood circulation and  prevent blockage  of milk production channels from facilitating the expenditure of milk. At the same time, oxytocin massage can stimulate the secretion of the hormone oxytocin (letdown reflex) so that milk comes out. This research analyzes the effect of a  combination of breastcare and  oxytocin massage on breastfeeding mothers on infant weight gain. This research is a quasi-experimental study with a pre-post test control design. Sampling took as consecutive sampling. The results showed that there were significant mean differences in infant weight gain between the treatment and control groups (p <0.05). The results of this study  expected to contribute to midwifery as a non-pharmacological effort to increase milk production  which will have a positive impact on infant weight so that it can support the government's efforts to increase exclusive breastfeeding coverage and reduce infant mortality and morbidity.